Research needs in systems engineering: Report from a University of Alabama in Huntsville workshop. Issue 2 (18th June 2019) - White, Christopher J.; Mesmer, Bryan L.
Abstract: The success of systems engineering (SE) efforts to solve development issues benefit from the mutually advantageous relationship between academia and practice. This relationship can be threatened by lag in adoption and differences in focus between the two worlds. In an effort to help maintain alignment between SE research and practice, a 2‐day workshop was held at the University of Alabama in Huntsville on research needs in SE. The workshop was attended by individuals from academia, the Department of Defense, NASA, and the aerospace industry. This paper presents summaries of the discussions that took place, as well as possible research questions informed by the results of the workshop. The workshop consisted of an introductory roundtable and three breakouts sessions focusing on requirements, verification, and validation; configuration and data management; and systems acquisition and design. Several topics emerged as important concepts for future research, and research questions were developed relating to model‐based systems engineering (MBSE), requirements, modeling, sociotechnical issues, and education.